Recent advances in flexible pressure/strain sensors using carbon nanotubes - Ma, Chan; Zhou, Ruiyun; Xie, Lijuan (International Journal of Agricultural and Biological Engineering, 2022)
In the context of the information society, wearable devices show broad prospects in the fields of vital signs monitoring, plant health monitoring, artificial electronic skin. As an inseparable part of wearable devices, flexible pressure/strain sensors have attracted wide attention. Structures and active materials are core factors affecting sensing performance. For the past few years, the introduction of carbon materials, especially carbon nanotubes, has provided more possibilities for improving performance. Great efforts have been devoted to researching pressure/strain sensors based on carbon nanotubes with excellent performance or unique features. Herein, the process in recent years in novel flexible pressure/strain sensors based on carbon nanotubes is reviewed. Fabrication strategies are discussed because it suggests sensing performance with significant differences and gives additional features like biodegradability and corrosion resistance to sensors. Furthermore, the scope of application has been extended to plant monitor, except for common human movement monitor. This review can help the researchers compare the influence of different fabrication strategies on the sensing performance and provide references for fabricating sensors in different applications.Keywords: carbon nanotube, flexible sensor, strain sensor, pressure sensorDOI: 10.25165/j.ijabe.20221502.7364Citation: Ma C, Zhou RY, Xie L J. Recent advances in flexible pressure/strain sensors using carbon nanotubes. Int J Agric & Biol Eng, 2022; 15(2): 1–12.